2009
DOI: 10.1161/atvbaha.108.179333
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hydrogen Sulfide in the Development of Atherosclerotic Lesions in Apolipoprotein E Knockout Mice

Abstract: Objective-We explored the effect of hydrogen sulfide (H 2 S) on atherosclerotic progression, particularly on intracellular adhesion molecule-1 (ICAM-1) in apolipoprotein-E knockout (apoE Ϫ/Ϫ ) mice and human umbilical vein endothelial cells (HUVECs). Methods and Results-ApoEϪ/Ϫ mice were treated with sodium hydrosulfide (NaHS) or DL-propargylglycine (PPG); HUVECs were pretreated with NaHS. Compared with control mice, apoE Ϫ/Ϫ mice showed decreased plasma H 2 S level and aortic H 2 S production but increased pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
271
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(294 citation statements)
references
References 37 publications
(22 reference statements)
17
271
1
1
Order By: Relevance
“…H 2 S is produced in vivo from L-cysteine by the action of two main enzymes, CSE and cystathionine ␤-synthase (5-7). Exogenous H 2 S supplementation reduces blood pressure, decreases atherosclerotic plaque size compared with those of controls in apolipoprotein E knock-out mice, and prevents progression of diabetic nephropathy in spontaneously hypertensive rats and endothelial dysfunction in diabetic rats (22,23). Several studies demonstrate that H 2 S is an antioxidant that regenerates GSH and lowers oxidative stress (5)(6)(7)11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H 2 S is produced in vivo from L-cysteine by the action of two main enzymes, CSE and cystathionine ␤-synthase (5-7). Exogenous H 2 S supplementation reduces blood pressure, decreases atherosclerotic plaque size compared with those of controls in apolipoprotein E knock-out mice, and prevents progression of diabetic nephropathy in spontaneously hypertensive rats and endothelial dysfunction in diabetic rats (22,23). Several studies demonstrate that H 2 S is an antioxidant that regenerates GSH and lowers oxidative stress (5)(6)(7)11).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D may upregulate insulin receptors and activate peroxisome proliferatoractivated receptor ␥ expression (28). Vitamin D may increase the synthesis of calbindin, which can alter calcium-dependent insulin secretion by pancreatic ␤-cells (22). Vitamin D can also affect IL-12 secretion via inhibition of NF-B in macrophages and dendritic cells, as well as inhibition of proinflammatory cytokine secretion by modulation of monocyte/macrophage and preadipocyte differentiation (1, 28 -31).…”
Section: Vitamin D H 2 S and Glucose Metabolismmentioning
confidence: 99%
“…H 2 S plays an important role in the regulation of systemic and pulmonary circulation [25][26][27][28][29][30] . Olson et al showed that in rat pulmonary arteries, NaHS produced a transit constriction followed by relaxation for 20 to 30 min, which was then followed by a second constriction [5] .…”
Section: Discussionmentioning
confidence: 99%
“…CSE expression and H 2 S production were significantly decreased during the development of balloon injury-induced neointimal hyperplasia in the rat carotid artery, and that exogenous H 2 S significantly reduced neointimal lesion formation [158]. Treatment of apoE-KO mice with NaHS decreased, and with PPG increased, atherosclerotic lesion size [159]. NaHS (100 µmol/L for 12 hrs) inhibited ICAM-1 expression in TNF-alpha-induced HUVECs via the NF-kB pathway [159].…”
Section: The Roles Of H 2 S and No In Atherosclerosismentioning
confidence: 99%
“…Treatment of apoE-KO mice with NaHS decreased, and with PPG increased, atherosclerotic lesion size [159]. NaHS (100 µmol/L for 12 hrs) inhibited ICAM-1 expression in TNF-alpha-induced HUVECs via the NF-kB pathway [159]. Moreover, NaHS administration concentration-dependently (50-200 µM) reduced CX3CR1 and CX3CL1 expression in mouse peritoneal macrophages as well as CX3CR1-mediated chemotaxis [160].…”
Section: The Roles Of H 2 S and No In Atherosclerosismentioning
confidence: 99%